Regression technique: model to predict causal relationship between variables - Hirudayaraj, Gladius Jennifer; Das, Bagavan (International Journal Of Community Medicine And Public Health, 2017)
Medical research is aim to quantify the disease magnitude and establish association between the study variables. Regression is the technique, which will not only find the correlation but also predict how much are the strength of relationship between variables. This article aims, to discuss various types of regression techniques such as Linear Regression, Multiple Regression, Logistic Regression, Meta regression and spatial regression and Regression Imputation with assumptions and models. This article is to sensitize doctors and post-graduate medical students about this useful analytical technique.